Paternity Fraud in Nigeria: Ethical, Legal, Cultural, and Social Dimensions - Metuonu, Iheanacho Chukwuemeka (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Paternity fraud is a situation where a woman misleads or deceives a man into believing and accepting he is the biological father of a child. It is a rampant, growing, but underexplored issue in Nigeria with significant ethical, legal, and social consequences. Despite anecdotal evidence suggesting a high prevalence—up to 40% in some private DNA testing centers—there is a critical research gap in empirical data and legal provisions addressing paternity fraud. Existing family laws do not explicitly recognize paternity fraud, leading to inconsistent judicial outcomes and inadequate restitution for affected individuals. Cultural taboos connected to paternity testing further complicate the issue, as requesting a DNA test is often perceived as distrustful or disrespectful, challenging deeply held cultural values. This study examines the ethical dilemmas, legal gaps, cultural influences, and social impacts of paternity fraud in Nigeria. Using a mixed-methods approach, it analyzes legal statutes, court cases, and cultural narratives while incorporating survey and interview data from affected individuals and experts. Findings reveal that economic insecurity, societal pressure on women to bear children, and restricted access to affordable DNA testing contribute to the problem. The study recommends specific legal reforms, increased accessibility to DNA testing, and public awareness initiatives to mitigate paternity fraud’s impact. Addressing this issue through legal, social, and cultural interventions will promote justice, ethical responsibility, and family stability in Nigeria.